2022
DOI: 10.1101/2022.12.01.518804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Low-level Persistent Infection on maintenance of immunity by CD4 T cell subsets and Th1 cytokines

Abstract: CD4 T cells are required, along with antibodies, for complete protection from blood-stage infection with Plasmodium spp., which cause malaria. Without continuous exposure, as on emigration of people from endemic areas, protection from malaria decays. As in other persistent infections, low-level P. chabaudi protects the host from re-infection at two months post-infection, a phenomenon termed premunition. Premunition is correlated with T cell responses, rather than antibody levels. We previously showed that whil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…IFN-γ production has been previously reported in MCMV and HCMV infection during the period coinciding with latency [23]. Data from our laboratory and others establishes that IFN-γ expression during persistent P. chabaudi infection, or recombinant IFN-γ also promote protection from heterologous re-infection at day 200 [12,44]. It was also reported that rIFN-γ increased the number of polyclonal Tem at day 200 after P. chabaudi infection [44].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…IFN-γ production has been previously reported in MCMV and HCMV infection during the period coinciding with latency [23]. Data from our laboratory and others establishes that IFN-γ expression during persistent P. chabaudi infection, or recombinant IFN-γ also promote protection from heterologous re-infection at day 200 [12,44]. It was also reported that rIFN-γ increased the number of polyclonal Tem at day 200 after P. chabaudi infection [44].…”
Section: Discussionsupporting
confidence: 76%
“…To test the potential of an MCMV-based booster vaccine, mice were vaccinated with live P. chabaudi AS infection followed by sub-curative doses of chloroquine and then boosted with MCMV-BAC or MCMV-B5 140 days later, as schematically depicted in Fig 3A . As vaccineinduced protection decays by day 200, we tested MCMV boosters for protection from heterologous re-infection with P. chabaudi AJ at day 200, which corresponds to 60 days after boosting. This timing was chosen on the basis that neither immunity nor the T cell response to live vaccination has completely decayed by day 120 [3,12], and that the MCMV infection is below detectable by day 60 [24], though we expected it to show prolonged stimulatory capacity at this timepoint [22].…”
Section: Boosts Long-term Protection Of Live Malaria Vaccinementioning
confidence: 99%
See 1 more Smart Citation